When blood pressure refuses to budge: exploring the complexity of resistant hypertension - Champaneria, Meeti Keyur; Patel, Rushi Sanjaykumar; Oroszi, Terry L. (Frontiers in Cardiovascular Medicine, 2023)
Resistant hypertension, defined as blood pressure that remains above goal despite using three or more antihypertensive medications, including a diuretic, affects a significant proportion of the hypertensive population and is associated with increased cardiovascular morbidity and mortality. Despite the availability of a wide range of pharmacological therapies, achieving optimal blood pressure control in patients with resistant hypertension remains a significant challenge. However, recent advances in the field have identified several promising treatment options, including spironolactone, mineralocorticoid receptor antagonists, and renal denervation. In addition, personalized management approaches based on genetic and other biomarkers may offer new opportunities to tailor therapy and improve outcomes. This review aims to provide an overview of the current state of knowledge regarding managing resistant hypertension, including the epidemiology, pathophysiology, and clinical implications of the condition, as well as the latest developments in therapeutic strategies and future prospects.